(3fXe GdSdhc aj eUGFO Gdedhcs - (3eMeO Hf eMeO Hf eMeO Hf GdMSf GdLPGej GdaGQbj GdeUQj, GHf fHGJg , LeGd GdOjf CHh HcQ,J (B768 (3g` s
(3ChdgG (B:s
(3HYO GdHSedI hGdOjHGLI GfKj TPj GdQhV Ydi aVd GdSMH hGSJedJ HGdhTj GQOGa GdcJH s
(3BNQgG (B:s
(3jG fGUQ GdOjf OYGA eGQM eG Hjf QhVGJ hLGeY MSHc eKdj aj GdGfGe TGYQkG hMSH TYQj bhI hfGUQ s
(3Vef eLehY , JQJjHgG (B: 15s
(3ChQGb aj GdCOH fbdkG Yf HgLI GdeLGdS dGHf YHO GdHQ hGddGdGJ GdSeYjIs
(3HgG fXGe GdJYbjHI hjJdhgGs
(3bQf GdfSN (B:s
(3GdbQf GdKGfj YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B7 - (3U (B38 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B11 - (3U (B273 ; (3gOjI GdYGQajf ddHZOGOi(B: (3L (B2 - (3U (B164s
Keywords: (3eJaQbGJs